Spectral characteristics of scintillations producing ionospheric irregularities in the Indian region - Banola, S.; Pathan, B.M.; Rao, D.R.K.; Chandra, H. (My University, 2005)
VHF amplitude scintillations were recorded at Tirunelveli (8.7°N, 77.7°E; 0.6°N dip Latitude), Pondicherry (12°N, 79.1°E; 4.4°N dip Latitude) and Mumbai, (19°N, 73°E; 13.5°N dip Latitude) for the years 1992–1996 using the 250 MHz radio beacon from the geostationary satellite FLEETSAT (73°E). The recorded digital scintillation data for few nights are analyzed to estimate scintillation index (S 4), fade rates, auto-correlation functions and power spectral densities for every 2.5 minute sample during the period of the scintillation activity. The power spectral slopes are shallower for the scintillation at the generation phase and steeper towards the decay phase, which indicates the erosion of smaller scale sizes towards the decay phase.
Keywords: Equatorial ionosphere; Ionospheric irregularities; VHF scintillations; Fade rate; Indian region